1999
DOI: 10.1007/bf02349890
|View full text |Cite
|
Sign up to set email alerts
|

A critical review on the stability constants of the fluoride complexes of actinides in aqueous solution and their correlation with fundamental properties of the ions

Abstract: Literature data on the stability constants of the fluoride complexes of the actinides in different oxidation states have been compiled. In order to have a reasonable inter-comparison, the stability constant ([31) values obtained in diverse ionic strength media are converted to so called thermodynamic stability constants, [3 ~ using the DAVIES equation (a modification of Debye-Huckel equation). A correlation of the [3 ~ values with the fundamental properties of the actinide ions using various models available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…A critical review of the literature data on the stability constants of the fluoride complexes of various metal ions in different oxidation states has been presented by Chaudhari et al 51 Zr forms the most stable complex (log β1-8.27) with fluoride among all other elements and hence, responsible for severe interference. To suppress the effect of fluoride, the suppressing agent should be chosen in such a way that it could form quite stable complex with fluoride.…”
Section: Selection Of the Masking Agentmentioning
confidence: 99%
“…A critical review of the literature data on the stability constants of the fluoride complexes of various metal ions in different oxidation states has been presented by Chaudhari et al 51 Zr forms the most stable complex (log β1-8.27) with fluoride among all other elements and hence, responsible for severe interference. To suppress the effect of fluoride, the suppressing agent should be chosen in such a way that it could form quite stable complex with fluoride.…”
Section: Selection Of the Masking Agentmentioning
confidence: 99%
“…However, complexation of Pu by citrate at low pH is expected to be suppressed due to the weakly acidic nature of the citric acid leading to its being protonated. Table 8 of Chaudhuri et al (1999);7: Sawant et al (1990);8: Xia et al (2010) This brief overview provides information on potential Pu-complexing eluting agents to amend the 0.5 M HNO 3 solution currently used to strip and regenerate the sRF resin. The candidate eluting agents are shown in Figure 17.…”
Section: Potential Pu Stripping Agentsmentioning
confidence: 99%
“…Hydrofluoric acid (HF) strongly complexes with Pu in various oxidation states and is often used in combination with HNO 3 to facilitate Pu oxide dissolution (Barney 1977;Tallent 1976). The complexation behaviors of Pu(IV) and Pu(III) with fluoride have been extensively investigated and several studies report association constants obtained under different conditions and different experimental methods (Chaudhuri et al 1999). Only formation of the 1:1 PuF 3+ complex has been examined in the majority of the studies and reported values demonstrate good agreement across the tested methods.…”
Section: Potential Pu Stripping Agentsmentioning
confidence: 99%
“…Anionic complexes of AnO þ 2 and AnO 2þ 2 have also been studied (Ahrland and Kullberg, 1971b;Inoue and Tochiyama, 1985), and pentagonal bipyramidal UO 2 F 3À 5 forms at high fluoride concentrations (Vallet et al, 2002). Stability constants and thermodynamic parameters for the formation of the fluoro complexes of actinides in various oxidation states are summarized in (Chaudhuri et al, 1999). Stability constants for the fluoro complexes of the pentavalent actinides have been reported only for protactinium (Guillaumont, 1966;Kolarich et al, 1967) and neptunium (as assessed by Lemire et al, 2001).…”
Section: Complexes With Inorganic Ligandsmentioning
confidence: 97%